2011
DOI: 10.1111/j.1365-2036.2011.04732.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine (5‐aminosalicylic acid) alters faecal bacterial profiles, but not mucosal proteolytic activity in diarrhoea‐predominant irritable bowel syndrome

Abstract: SUMMARY BackgroundImbalances in gut luminal bacteria may contribute to the pathogenesis of irritable bowel syndrome (IBS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 47 publications
3
56
1
2
Order By: Relevance
“…It should be acknowledged that differences between the microbial communities may partly be the consequence of the use of anti-inflammatory drugs, since a recent study showed that melsalazine affected the fecal bacterial community composition in patients with inflammatory bowel syndrome (2). In the present study, four out of six UC patients in remission received melsalazine, whereas all the UC patients in relapse received the drug.…”
Section: Discussionmentioning
confidence: 62%
“…It should be acknowledged that differences between the microbial communities may partly be the consequence of the use of anti-inflammatory drugs, since a recent study showed that melsalazine affected the fecal bacterial community composition in patients with inflammatory bowel syndrome (2). In the present study, four out of six UC patients in remission received melsalazine, whereas all the UC patients in relapse received the drug.…”
Section: Discussionmentioning
confidence: 62%
“…In a 20-patient study, general well-being was improved, but the colonic symptoms did not change (56). In a trial involving 12 IBS-D patients, mesalazine (1.5 g, 2 times per day) was associated with symptomatic response of global relief, decreased number of days with discomfort, and increased bowel movement satisfaction in 8 patients (57). Mesalazine induced relief of pain and diarrhea in patients with these predominant symptoms in a third trial (58), but efficacy was not replicated in a recent small trial (59).…”
Section: Chronic Diarrheamentioning
confidence: 99%
“…Dysbiosis has been illustrated in both patients with Crohn's disease (CD) and ulcerative colitis (UC) during remission [50][51][52]. Even standard IBD therapies can significantly alter the gut microbiome, evidenced by nearly a 50% reduction in the bacterial load with mesalamine (5-aminosalicylic acid, mesalazine) administration and also an amplification of the dysbiosis with antibiotics [52,53].…”
Section: Genetic and Microbial Interactions In Inflammatory Bowel Dismentioning
confidence: 99%